2018
DOI: 10.1155/2018/9408715
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low-Calorie Pumpkin Jams Fortified with Soybean on Diabetic Rats: Study of Chemical and Sensory Properties

Abstract: This research investigated the chemical analysis and sensory evaluation of low-calorie formulated pumpkin jams after storage for six months and the effects of the consumption of low-calorie jams on diabetic rats. Pumpkin jam with sucrose, fructose, stevia, and aspartame sweeteners and soybean was prepared and stored at 10°C for six months. Rats were divided into group 1 (negative control), group 2 (positive diabetic groups), and groups 3, 4, and 5 (diabetic groups treated with 10% sucrose, fructose, and stevia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
2
3
0
Order By: Relevance
“…The results of the proximate analysis also showed that fortification of normal fruit jams with soybean significantly increased the crude protein, fat content and decreased the carbohydrate content. These results agree with Alsuhaibani and Al-Kuraieef (2018), who recorded an increase in protein and fat content with a decrease in carbohydrate content of an ordinary pumpkin jam when soybean was added. However, the value of the fat content reported by Alsuhaibani and Al-kuraieef (2018) is close to the values observed in the present study but the value of the protein content observed in this study is far from the value reported by Alsuhaibani and Al-kuraieef (2018), for pumpkin jam fortified with soybean.…”
Section: Discussion Of Findingssupporting
confidence: 92%
See 3 more Smart Citations
“…The results of the proximate analysis also showed that fortification of normal fruit jams with soybean significantly increased the crude protein, fat content and decreased the carbohydrate content. These results agree with Alsuhaibani and Al-Kuraieef (2018), who recorded an increase in protein and fat content with a decrease in carbohydrate content of an ordinary pumpkin jam when soybean was added. However, the value of the fat content reported by Alsuhaibani and Al-kuraieef (2018) is close to the values observed in the present study but the value of the protein content observed in this study is far from the value reported by Alsuhaibani and Al-kuraieef (2018), for pumpkin jam fortified with soybean.…”
Section: Discussion Of Findingssupporting
confidence: 92%
“…These results agree with Alsuhaibani and Al-Kuraieef (2018), who recorded an increase in protein and fat content with a decrease in carbohydrate content of an ordinary pumpkin jam when soybean was added. However, the value of the fat content reported by Alsuhaibani and Al-kuraieef (2018) is close to the values observed in the present study but the value of the protein content observed in this study is far from the value reported by Alsuhaibani and Al-kuraieef (2018), for pumpkin jam fortified with soybean. The observed variation in the protein content might have been as a result of geographic, climatic and seasonal variations as well as different fruits and analytical methods used.…”
Section: Discussion Of Findingssupporting
confidence: 92%
See 2 more Smart Citations
“…A similar increasing trend was noticed for dough stability by increasing the level of fortificant in wheat flour. These results can be justified by a recent work of Alsuhaibani (2018), who reported that bread supplemented with egg and oyster shells indicated higher values of water absorption, DDT and dough stability in comparison to control. However, in contrast to present findings, Salem et al (2013) have designated a reduction in dough development time and dough stability with chicken eggshell addition in wheat flour.…”
Section: Farinographic Properties Of Calcium Fortified Flourmentioning
confidence: 78%